2008
DOI: 10.1073/pnas.0712110105
|View full text |Cite
|
Sign up to set email alerts
|

The Foldback -like element Galileo belongs to the P superfamily of DNA transposons and is widespread within the Drosophila genus

Abstract: Galileo is the only transposable element (TE) known to have generated natural chromosomal inversions in the genus Drosophila. It was discovered in Drosophila buzzatii and classified as a Foldback-like element because of its long, internally repetitive, terminal inverted repeats (TIRs) and lack of coding capacity. Here, we characterized a seemingly complete copy of Galileo from the D. buzzatii genome. It is 5,406 bp long, possesses 1,229-bp TIRs, and encodes a 912-aa transposase similar to those of the Drosophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 47 publications
(62 reference statements)
3
60
1
Order By: Relevance
“…The labiality in structural morphologies is not unique to Phantom elements; recent studies have shown that the FB element, Galileo, is a member of the P-element superfamily where the canonical families display short TIRs (Marzo et al 2008). Since the TIRs typically contain the transposase binding sites required for the cleavage and integration of DNA transposons (Craig et al 2002), we propose that structural variation might evolve to avoid recognition by the host.…”
Section: Discussionmentioning
confidence: 99%
“…The labiality in structural morphologies is not unique to Phantom elements; recent studies have shown that the FB element, Galileo, is a member of the P-element superfamily where the canonical families display short TIRs (Marzo et al 2008). Since the TIRs typically contain the transposase binding sites required for the cleavage and integration of DNA transposons (Craig et al 2002), we propose that structural variation might evolve to avoid recognition by the host.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the inferred phylogenetic relationship of DINE-1 paralogues from several Drosophila species suggests vertical transmission as the major mechanism for DINE-1 propagation. Likewise, analysis of the Galileo ARTICLES and 1360 transposons reveals a widespread but discontinuous phylogenetic distribution for both families, notably with both families absent in the geographically isolated Hawaiian species, D. grimshawi 52 . These results are consistent with an ancient origin of the Galileo and 1360 families in the genus and subsequent horizontal transfer and/or loss in some lineages.…”
Section: Gelbart Personal Communication) (Supplementary Information mentioning
confidence: 99%
“…Unequivocal evidence for the implication of transposable elements (TEs) has been found in three Drosophila buzzatii inversions: 2j (Cáceres et al 1999(Cáceres et al , 2001, 2q 7 (Casals et al 2003), and 2z 3 (Delprat et al, in preparation). These three inversions were generated by non-allelic homologus recombination (or ectopic recombination) between copies of the transposon Galileo (Marzo et al 2008) inserted in opposite orientation at two distant chromosomal sites. A polymorphic inversion of Drosophila pseudoobscura, Arrowhead, was also generated by ectopic recombination between 128 and 315-bp repeats, yet the nature of these repeats and their possible relation to an unidentified TE are obscure (Richards et al 2005).…”
Section: Introductionmentioning
confidence: 99%